Аdministrative-normative bases of system of centers of free legal aid system fctivity - Strukova, Kristina (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
In the article administrative-normative nature, legal nature, role and place of the system of centers of free legal aid system of rights and freedoms of citizens, given the complex characteristics of the state and social institutions that should ensure the implementation of the right. A draft amendments to the legislation of Ukraine on the study.